Cor triatriatum: Un hallazgo común en dos pacientes - Blanco Pérez, Yiliam; Morocho Minchala, Mariana E.; Nápoles Martínez, Liudmila; Prieto Guerra, Maidelis (CorSalud, 2023)
Cor triatriatum: Un hallazgo común en dos pacientes